The Pacific Alliance Towards a Strategy on Digital Economy? (2020)
Countries of the Pacific Alliance (PA) share a common interest in the development of a regional regulatory framework that can give impetus to the dynamism of the embryonic digital economy in the region. The trend towards the progressive implementation of new and stricter rules on e-commerce fosters increments on foreign investment and generation of spill over effects. However, the preference for the models inspired by the FTAs negotiated by the United States, as well as a clear predilection for self-regulation schemes, reflect the dominant role of the private sector in the negotiations within the PA. This scenario raises serious doubts about the institutional model of the Alliance and its suitability to frame sustainable solutions to the complex social and economic consequences derived from the deepening of the digital economy.